Water T2 could predict functional decline in patients with dysferlinopathy. Issue 6 (4th September 2022) - Moore, Ursula; Caldas de Almeida Araújo, Ericky; Reyngoudt, Harmen; Gordish‐Dressman, Heather; Smith, Fiona E.; Wilson, Ian; James, Meredith; Mayhew, Anna; Rufibach, Laura; Day, John W.; Jones, Kristi J.; Bharucha‐Goebel, Diana X.; et al.
Abstract: Background: Water T2 (T2H2O ) mapping is increasingly being used in muscular dystrophies to assess active muscle damage. It has been suggested as a surrogate outcome measure for clinical trials. Here, we investigated the prognostic utility of T2H2O to identify changes in muscle function over time in limb girdle muscular dystrophies. Methods: Patients with genetically confirmed dysferlinopathy were assessed as part of the Jain Foundation Clinical Outcomes Study in dysferlinopathy. The cohort included 18 patients from two sites, both equipped with 3‐tesla magnetic resonance imaging (MRI) systems from the same vendor. T2H2O value was defined as higher or lower than the median in each muscle bilaterally. The degree of deterioration on four functional tests over 3 years was assessed in a linear model against covariates of high or low T2H2O at baseline, age, disease duration, and baseline function. Results: A higher T2H2O at baseline significantly correlated with a greater decline on functional tests in 21 out of 35 muscles and was never associated with slower decline. Higher baseline T2H2O in adductor magnus, vastus intermedius, vastus lateralis, and vastus medialis were the most sensitive, being associated bilaterally with greater decline in multiple timed tests. Patients with a higher than median baseline T2H2O (>40.6 ms) in the right vastus medialis deteriorated 11 points more on the North Star Ambulatory Assessment for Dysferlinopathy and lost an additional 86 m on the 6‐min walk than those with a lower T2H2O (<40.6 ms). Optimum sensitivity and specificity thresholds for predicting decline were 39.0 ms in adductor magnus and vastus intermedius, 40.0 ms in vastus medialis, and 40.5 ms in vastus lateralis from different sites equipped with different MRI systems. Conclusions: In dysferlinopathy, T2H2O did not correlate with current functional ability. However, T2H2O at baseline was higher in patients who worsened more rapidly on functional tests. This suggests that inter‐patient differences in functional decline over time may be, in part, explained by different severities of the active muscle damage, assessed by T2H2O measure at baseline. Significant challenges remain in standardizing T2H2O values across sites to allow determining globally applicable thresholds. The results from the present work are encouraging and suggest that T2H2O could be used to improve prognostication, patient selection, and disease modelling for clinical trials.